Solar cell back panel
By adopting the structure of hydrophobic high weather-resistant low temperature fluorine film layer, hydrolytic adhesive layer, liquid crystal aromatic polyester polymer film layer, hydrolytic polyethylene terephthalate layer and film bonding layer on the back panel of the solar cell, the problems of insufficient water vapor transmission rate and coating delamination of the existing back panel are solved, and efficient water vapor barrier and long-life component protection are achieved.
Patent Information
- Application Number
- CN202421543658.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2034-07-02
AI Technical Summary
The water vapor transmission rate of the existing solar cell back panel is insufficient, which cannot meet the requirements of N-type batteries for high water resistance, and the coating back panel is prone to coating delamination problems after aging of high temperature and high humidity.
The structures of hydrophobic high weather-resistant low temperature fluorine film layer, hydrolyzed adhesive layer, liquid crystal aromatic polyester polymer film layer, hydrolyzed polyethylene terephthalate layer and film bonding layer are adopted in sequence. The synergistic effect of these layers is achieved to achieve excellent water vapor barrier performance and maintain stable performance under high temperature and high humidity conditions.
It realizes excellent water vapor barrier performance of the solar cell backplane, and has basically no attenuation after high temperature and high humidity aging. It can effectively protect components, extend service life, and avoid insulation problems.
Smart Images

Figure CN222750784U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to a solar cell back plate and belongs to the photovoltaic field. Background Art
[0002] With the development of photovoltaic cell technology, the rapid iteration of N-type cell technology has brought about changes in the packaging requirements of the module end. N-type cells are more sensitive to water vapor, so they also put forward higher water-blocking requirements for module packaging. The solar cell backplane is an important component of the photovoltaic module and plays a vital role in water blocking.
[0003] The water vapor transmission rate (characterizing water barrier performance) of conventional solar cell backsheets is 2g / m 2 ×d, which cannot meet the requirements of high water resistance. Currently, there are three main technical solutions for high water resistance backplanes on the market:
[0004] One is to add a layer of aluminum foil to the original conventional "sandwich" structure backplane. Aluminum foil has good water vapor barrier properties, so that its backplane products can achieve good water vapor barrier effect. Aluminum foil backplane technology is relatively mature, but the use of aluminum foil backplane has insulation problems at the opening and edge of its components.
[0005] The second is to coat the middle layer of the original backplane, namely the polyethylene terephthalate (PET) layer, or add an extra layer of coated PET to improve its water vapor barrier performance. The coating technologies of coated backplanes are mainly: 1) vacuum evaporation, the production speed of this technology can reach 100m / min, but the water vapor barrier of the coating is biased; 2) atomic layer deposition ALD, this technology has an extremely slow production speed of only 1-2m / min, which brings higher production costs; 3) magnetron sputtering (a type of physical vapor deposition), the production speed is 5-10m / min, and the barrier property is relatively good; 4) plasma enhanced chemical vapor deposition PECVD, this technology requires high temperature and cannot be achieved on PET. The performance problem of coated backplanes is mainly the delamination of the coating after high temperature, high pressure and wet heat aging, which leads to the failure of the protective performance of the backplane. This problem has not been well solved yet.
[0006] The third is to add a layer of polymer water-blocking film to the original backplane, but the water-blocking performance of conventional polymer materials is at least 1g / m 2 ×d, the water-blocking effect of its back panel still cannot meet the use requirements. Utility Model Content
[0007] In order to solve the above technical problems, the purpose of the utility model is to provide a solar cell back panel, which has excellent water vapor barrier performance and has basically no attenuation in product performance after high temperature and high humidity aging.
[0008] To achieve the above-mentioned purpose, the utility model provides a solar cell back panel, which includes a hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer, a first anti-hydrolysis adhesive layer, a liquid crystal aromatic polyester polymer film layer, a second anti-hydrolysis adhesive layer, an anti-hydrolysis polyethylene terephthalate layer and a film bonding layer which are stacked in sequence.
[0009] Based on the above structural setting, firstly, the solar cell backplane of the utility model has excellent water vapor barrier performance, and the product performance is basically not attenuated after high temperature and high humidity aging. It is subsequently used on the back of the N-type battery module to effectively prevent water vapor from entering the module and affecting the power generation efficiency of the module, thereby making the solar cell module operate effectively. The hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer is arranged on the outer layer of the backplane to effectively block the entry of ultraviolet rays, and protect the inner liquid crystal aromatic polyester polymer film layer from being affected by ultraviolet rays and aging, so that it still has good water resistance; in particular, the liquid crystal aromatic polyester polymer film layer is arranged on the outside of the hydrolysis-resistant polyethylene terephthalate layer, which can effectively prevent the entry of water vapor and protect the hydrolysis-resistant polyethylene terephthalate layer from being affected by water vapor and hydrolyzed and aged, resulting in performance attenuation.
[0010] Secondly, the utility model solar cell backsheet plays a good role in protecting and supporting the components. On the one hand, the utility model solar cell backsheet has good high weather resistance and low temperature resistance, and it can still show excellent mechanical properties in harsh environments, and will not have undesirable problems such as film brittleness and cracking. On the other hand, the utility model adhesive film bonding layer is arranged on the inner layer of the backsheet, which can greatly improve the bonding between the backsheet and the ethylene-vinyl acetate copolymer (EVA) film in the component in the subsequent assembly, and the product has a long service life.
[0011] Furthermore, in the above structure of the utility model, the anti-hydrolysis polyethylene terephthalate layer and the liquid crystal aromatic polyester polymer film layer are cooperatively arranged, and the above excellent water vapor barrier performance can be achieved without including aluminum foil, and there is no insulation problem. The insulation of the product can even be further improved, thereby providing double-layer insulation protection for the components in the future.
[0012] In addition, the structure of the above-mentioned solar cell backplane can subsequently meet the production requirements through a conventional composite backplane production line without the need to add or modify equipment. It is easier to obtain than the two technical routes of aluminum foil composite backplane and coated backplane. The processing and production speed of this technical route can generally reach ≥80m / min, with high production efficiency and better prospects for industrial application.
[0013] It is noted that the above-mentioned hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer, the first anti-hydrolysis adhesive layer, the liquid crystal aromatic polyester polymer film layer, the second anti-hydrolysis adhesive layer, the anti-hydrolysis polyethylene terephthalate layer and the adhesive film bonding layer of the utility model are all known in the prior art in the field and can be directly commercially obtained. For example, fluorine films with hydrophobic, high weather resistance and low-temperature resistance can be used in the above-mentioned backplane of the utility model as a hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer. For example, polyethylene terephthalate films with anti-hydrolysis properties can be used in the above-mentioned backplane of the utility model as an anti-hydrolysis polyethylene terephthalate layer. For example, liquid crystal high molecular polymers (LCP for short, belonging to aromatic thermoplastic polyesters) can be used in the above-mentioned backplane of the utility model as liquid crystal aromatic polyester polymer films. For example, adhesive materials with anti-hydrolysis properties can be used in the above-mentioned backplane of the utility model as the first anti-hydrolysis adhesive layer and / or the second anti-hydrolysis adhesive. For example, any material that can bond adhesive films (such as ethylene-vinyl acetate copolymer adhesive films) can be used in the back panel of the utility model as the adhesive film bonding layer.
[0014] Specifically, in an optional embodiment, the hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer may be an M3 fluorine film with a hydrophobic outer surface purchased from Zhongtian Photovoltaic Materials Co., Ltd. In an optional embodiment, the plasma treatment parameters may be as follows: voltage 12kV-15kV, frequency 6-12kHz, working gas 2-5L / min, reaction medium 50-100mL / min, treatment time 5-10min, which can be achieved by those skilled in the art based on existing knowledge and will not be elaborated here.
[0015] In an optional embodiment, the materials of the first anti-hydrolysis adhesive layer and the second anti-hydrolysis adhesive layer can be purchased from Shanghai Chengying New Materials Co., Ltd. PA3018.
[0016] In an optional embodiment, the material of the hydrolysis-resistant polyethylene terephthalate layer can be purchased from Jiangsu Yuxing Film Technology Co., Ltd. as CY25R.
[0017] In an alternative embodiment, the material of the liquid crystal aromatic polyester polymer film layer can be purchased from Sumitomo Chemical Co., Ltd. as a liquid crystal aromatic polyester polymer film.
[0018] In an optional embodiment, the material of the adhesive film bonding layer can be purchased from Changzhou Weston Adhesive Materials Co., Ltd. as WSD-1555LF.
[0019] In order to further balance the comprehensive performance of the solar cell backsheet, in a preferred embodiment, the thickness of the adhesive film bonding layer is 5 to 20 μm. In some optional embodiments, the thickness of the adhesive film bonding layer can be 5 μm, 10 μm, 15 μm or 20 μm.
[0020] Furthermore, the thickness of the hydrophobic high weather resistance and low temperature resistance fluorine film layer is 10 to 40 μm. In some optional embodiments, the thickness of the hydrophobic high weather resistance and low temperature resistance fluorine film layer can be 10 μm, 20 μm, 30 μm or 40 μm.
[0021] Furthermore, the thickness of the liquid crystal aromatic polyester polymer film layer is 10-50 μm. In some optional embodiments, the thickness of the liquid crystal aromatic polyester polymer film layer may be 10 μm, 20 μm, 30 μm, 40 μm or 50 μm.
[0022] Further, the thickness of the hydrolysis-resistant polyethylene terephthalate layer is 200-400 μm. In some optional embodiments, the thickness of the hydrolysis-resistant polyethylene terephthalate layer may be 200 μm, 250 μm, 300 μm, 350 μm or 400 μm.
[0023] Furthermore, the thickness of the first anti-hydrolysis adhesive layer and the second anti-hydrolysis adhesive layer are each independently 5 to 20 μm, for example, each independently 5 μm, 10 μm, 15 μm or 20 μm.
[0024] Furthermore, the thickness ratio of the hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer, the first anti-hydrolysis adhesive layer and the liquid crystal aromatic polyester polymer film layer is 2-3:1:2-4.
[0025] Furthermore, the thickness ratio of the liquid crystal aromatic polyester polymer film layer, the second hydrolysis-resistant adhesive layer and the hydrolysis-resistant polyethylene terephthalate layer is 2-4:1:25-30.
[0026] Furthermore, the thickness ratio of the hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer to the adhesive film bonding layer is 2 to 4:1. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A schematic diagram of the structure of a solar cell back panel in one embodiment of the utility model is shown;
[0028] Figure 2 It shows the test result of water vapor transmission rate of the solar cell back sheet without aging treatment in Example 1 of the utility model;
[0029] Figure 3 The water vapor transmission rate test result diagram of the solar cell back sheet after PCT aging treatment in Example 1 of the utility model is shown;
[0030] Figure 4 The water vapor transmission rate test result diagram of the solar cell back panel without aging treatment in Comparative Example 1 of the present invention is shown.
[0031] Among them, 10-hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer; 20-first anti-hydrolysis adhesive layer; 30-liquid crystal aromatic polyester polymer film layer; 40-second anti-hydrolysis adhesive layer; 50-anti-hydrolysis polyethylene terephthalate layer; 60-film bonding layer. DETAILED DESCRIPTION
[0032] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the utility model, the technical solution of the utility model is now described in detail below, but it should not be understood as limiting the scope of implementation of the utility model.
[0033] Example 1
[0034] The structure of the solar cell back panel in this embodiment is as follows Figure 1 As shown, it includes a hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer 10, a first anti-hydrolysis adhesive layer 20, a liquid crystal aromatic polyester polymer film layer 30, a second anti-hydrolysis adhesive layer 40, an anti-hydrolysis polyethylene terephthalate layer 50 and a film adhesive layer 60 which are stacked in sequence. Among them:
[0035] The hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer 10 is an M3 fluorine film (purchased from Zhongtian Photovoltaic Materials Co., Ltd.) treated with surface plasma. Plasma treatment parameters: voltage 12 kV, frequency 9 kHz, working gas 3 L / min, reaction medium 50 mL / min, treatment time 6 min. The thickness of the hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer 10 is 30 μm.
[0036] The first anti-hydrolysis adhesive layer 20 has a thickness of 10 μm. Material source: PA3018 from Shanghai Chengying New Materials Co., Ltd.
[0037] The thickness of the liquid crystal aromatic polyester polymer film layer 30 is 30 μm. Material source: liquid crystal aromatic polyester polymer film from Sumitomo Chemical Co., Ltd.
[0038] The thickness of the second anti-hydrolysis adhesive layer 40 is 10 μm. Material source: PA3018 from Shanghai Chengying New Materials Co., Ltd.
[0039] The hydrolysis-resistant polyethylene terephthalate layer 50 has a thickness of 275 μm. Material source: CY25R from Jiangsu Yuxing Film Technology Co., Ltd.
[0040] The thickness of the adhesive film bonding layer 60 is 8 μm. Material source: WSD-1555LF from Changzhou Weston Adhesive Materials Co., Ltd.
[0041] Comparative Example 1
[0042] The structure of the solar cell back sheet of the comparative example includes a fluorine film layer, an anti-hydrolysis adhesive layer, an anti-hydrolysis polyethylene terephthalate layer, and a fluorine-containing coating layer which are stacked in sequence. Among them:
[0043] The thickness of the fluorine film layer is 30 μm. Material source: PV1010-WM from Hangzhou Fumo New Material Technology Co., Ltd.
[0044] The thickness of the anti-hydrolysis adhesive layer is 10 μm. Material source: PA3018 from Shanghai Chengying New Materials Co., Ltd.
[0045] The thickness of the hydrolysis-resistant polyethylene terephthalate layer is 275 μm. Material source: CY25R from Jiangsu Yuxing Film Technology Co., Ltd.
[0046] The thickness of the fluorine-containing coating is 8 μm. Material source: WSD-1555LF from Changzhou Weston Adhesive Materials Co., Ltd.
[0047] Characterization of water vapor barrier performance of backsheet:
[0048] Test method: GB / T 26253-2010.
[0049] PCT aging treatment conditions: treatment in a PCT aging box at a temperature of (121±0.5)°C, 2 atmospheres, and a humidity of 100%.
[0050] The water vapor transmission rate test results of the solar cell backsheet of Example 1 before PCT aging treatment are as follows: Figure 2 As shown, it is 0.1494g / m 2 ×d. The water vapor transmission rate test results of the solar cell backsheet of Example 1 after PCT aging treatment are as follows Figure 3 As shown, it is 0.1512g / m 2 ×d. The water vapor transmission rate test results of the solar cell backsheet of Comparative Example 1 before PCT aging treatment are as follows Figure 4 As shown, it is 1.48g / m 2 ×d. Figure 2 , Figure 3 and Figure 4 It can be shown that the solar cell back panel of the utility model has excellent water vapor barrier performance, and the water vapor transmission rate can reach ≤0.2g / m 2 ×d. And the product performance is basically not attenuated after high temperature and high humidity aging. It is subsequently used on the back of N-type battery modules to effectively prevent water vapor from entering the module and affecting the power generation efficiency of the module, so that the solar cell module can operate effectively.
Claims
1. A solar cell back sheet, characterized in that: The invention comprises a hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer (10), a first anti-hydrolysis adhesive layer (20), a liquid crystal aromatic polyester polymer film layer (30), a second anti-hydrolysis adhesive layer (40), an anti-hydrolysis polyethylene terephthalate layer (50) and a film adhesive layer (60) which are stacked in sequence.
2. The solar cell back sheet according to claim 1, characterized in that: The thickness of the hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer (10) is 10 to 40 μm.
3. The solar cell back sheet according to claim 1, characterized in that: The thickness of the liquid crystal aromatic polyester polymer film layer (30) is 10 to 50 μm.
4. The solar cell back sheet according to claim 1, characterized in that: The thickness of the hydrolysis-resistant polyethylene terephthalate layer (50) is 200-400 μm.
5. The solar cell back sheet according to claim 1, characterized in that: The thickness of the adhesive film bonding layer (60) is 5 to 20 μm.
6. The solar cell back sheet according to claim 1, characterized in that: The thickness of the first anti-hydrolysis adhesive layer (20) is 5 to 20 μm.
7. The solar cell back sheet according to claim 1, characterized in that: The thickness of the second anti-hydrolysis adhesive layer (40) is 5 to 20 μm.
8. The solar cell back sheet according to claim 1, characterized in that: The thickness ratio of the hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer (10), the first anti-hydrolysis adhesive layer (20) and the liquid crystal aromatic polyester polymer film layer (30) is 2-3:1:2-4.
9. The solar cell back sheet according to claim 1, characterized in that: The thickness ratio of the liquid crystal aromatic polyester polymer film layer (30), the second hydrolysis-resistant adhesive layer (40) and the hydrolysis-resistant polyethylene terephthalate layer (50) is 2-4:1:25-30.
10. The solar cell back sheet according to claim 1, characterized in that: The thickness ratio of the hydrophobic, highly weather-resistant and low-temperature-resistant fluorine film layer (10) to the adhesive film bonding layer (60) is 2 to 4:1.